Resistance to mainstreaming gender into the higher education curriculum. Issue 1 (February 2018) - Verge, Tània; Ferrer-Fons, Mariona; González, M José
Disregard of gender and of women's contributions in the higher education curriculum is still a widespread phenomenon. Building on feminist institutionalism, this article explores the forms and types of resistance that efforts to engender the higher education curriculum must contend with and discusses the ways in which resistance to curricular reform is entrenched in a web of both gender-specific and apparently gender-neutral academic informal (non-written) rules. In doing so, the authors use empirical evidence collected by an action-research project undertaken at a faculty of political and social sciences in a Catalan public university (Spain). The Spanish case is intriguing because mainstreaming gender in higher education has been prescribed by various national and regional laws that are nonetheless poorly implemented. The article also reflects on the positive feedback loop action-research projects can facilitate within gendered institutions such as universities and pinpoints the role of feminist agency in counteracting resistance to institutional change.